THE TIMELESS UTILITY OF DUKE TREADMILL SCORE: A PROGNOSTIC TOOL FOR CORONARY ARTERY DISEASE SEVERITY ASSESSMENT - Rai, Lajpat; Batra, Mahesh Kumar; Mengal, Muhammad Naeem; Kumar, Rajesh; Shah, Jehangir Ali; Memon, Aziz Ur Rehman; Haleem, Syed Mohammad; Sial, Jawaid Akbar; Saghir, Tahir; Karim, Musa (Journal of Ayub Medical College Abbottabad, 2025)
Background: This cross-sectional study aimed to evaluate the correlation between Duke Treadmill Score (DTS) and SYNTAX score and assess the role of DTS in predicting the severity of coronary artery disease (CAD) in patients with stable ischemic heart diseases. Methods: Conducted at a tertiary care cardiac center, the study included patients presenting to the outpatient department for the first time with angina and a positive exercise tolerance test (ETT), who underwent coronary angiogram. Correlation analysis was performed between DTS and SYNTAX score, and receiver operating characteristic (ROC) curve analysis was conducted for DTS to detect the presence (SYNTAX score ≥0) and severity (SYNTAX score ≥33) of CAD. Results: Out of 303 patients, 72.6% (220) were male, with a mean age of 53.31±10.11 years. CAD was confirmed in 79.9% (242) of patients. The mean SYNTAX score was 18.77±14.18, with 46.5% (141) categorized as low-risk, 27.1% as intermediate-risk, and 26.4% as high-risk. The mean DTS score was -6.09±4.5, with 13.9% categorized as high risk and the remaining 86.1% as intermediate or low risk. The Pearson correlation coefficient between DTS and SYNTAX score was -0.806 (p<0.001). The area under the curve (AUC) for DTS score in detecting the presence and severity of CAD was 0.992 [0.985–0.998] and 0.895 [0.860–0.929], respectively. Conclusion: A strong negative correlation was observed between SYNTAX score and DTS, highlighting the predictive value of DTS for assessing CAD severity. The DTS score demonstrated very high diagnostic accuracy in detecting the presence and severity of CAD.